2019
DOI: 10.1016/j.msard.2018.10.112
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the association between fatigue and fatigability in multiple sclerosis using cognitive control

Abstract: Background: Fatigue and cognitive dysfunction are two common symptoms experienced by patients with multiple sclerosis (MS). The relationship between subjective and objective fatigue (fatigability) in MS is poorly understood. Cognitive control tasks might be more conducive to fatigability and more likely to show associations between subjective and objective cognitive fatigue in MS. Objective: To study the association between objective fatigability, as induced by a cognitive control task called the Blocked Cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
0
21
1
Order By: Relevance
“…Therefore, whilst perceived fatigue change and reliable performance change may co-occur, it is not clear to what degree change in these is driven by fatigue per se. Contrary to other studies demonstrating relationships between perceived fatigue and cognitive performance fatigability (Cehelyk, Harvey, 2018, Wolkorte, Heersema, 2015 or motor fatigability (Loy, Taylor, 2017, Skurvydas, Brazaitis, 2011, Zijdewind, Prak, 2016, our results provide little general support for the role of fatigue variables in performance change. Whilst there was a link between cognitive impairment status and EDSS, neither had influence on perceived fatigue, fatigue change, or performance change, which are results that diverge from some other studies (Biberacher, Schmidt, 2018, Ghajarzadeh, Jalilian, 2013.…”
Section: Perceived Fatigue Change and Cognitive Performance Changecontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, whilst perceived fatigue change and reliable performance change may co-occur, it is not clear to what degree change in these is driven by fatigue per se. Contrary to other studies demonstrating relationships between perceived fatigue and cognitive performance fatigability (Cehelyk, Harvey, 2018, Wolkorte, Heersema, 2015 or motor fatigability (Loy, Taylor, 2017, Skurvydas, Brazaitis, 2011, Zijdewind, Prak, 2016, our results provide little general support for the role of fatigue variables in performance change. Whilst there was a link between cognitive impairment status and EDSS, neither had influence on perceived fatigue, fatigue change, or performance change, which are results that diverge from some other studies (Biberacher, Schmidt, 2018, Ghajarzadeh, Jalilian, 2013.…”
Section: Perceived Fatigue Change and Cognitive Performance Changecontrasting
confidence: 99%
“…An increasing drive to examine cognitive performance fatigability in MS has demonstrated that people with MS are vulnerable to cognitive performance change (Berard et al , 2018, Cehelyk et al , 2018, Claros-Salinas et al , 2013, Wolkorte et al , 2015. However, similarly to our understanding of perceived fatigue, the factors influencing cognitive performance change remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behaviorally, fatigability can be assessed through changes in reaction time, accuracy, and processing speed in simple alertness or vigilance tests over time. There are numerous studies showing increasing reaction times [25,33,38,39,45,47,59,60] and decreasing accuracy [32,41,42,43] with time-on-task, mostly assessed by administering simple reaction time tests such as the alertness subtest of the Test Battery for Attentional Performance (TAP) [61]. Claros-Salinas et al [33] measured fatigue in the TAP alertness task at three different time points during the course of one day.…”
Section: Objective Measurement Of Cognitive Fatiguementioning
confidence: 99%
“…Five studies especially examined subjective state-fatigue and their relationship to objective performance decline with time-on-task. Four studies found a positive relationship [25,43,47,60], while only one study did not [32]. Hence, longer reaction times with time-on-task as well as more omissions in the second half were shown to be associated with a greater feeling of momentary exhaustion [43,47,60].…”
Section: Relationship Between Objective and Subjective Fatiguementioning
confidence: 99%